The unfolded protein response - Mori, Kazutoshi (Henry Stewart Talks, 2012)
Molecular mechanism unfolded protein response, Physiological importance of the unfolded protein response, Intracellular signaling from the endoplasmic reticulum (ER) to the nucleus, Reasons for activation, Maintenance of homeostasis of the ER